Profile of the Scientific Organization in Scopus and Web of Science Databases. The Role of University Libraries in the Presentation of the Publication Activity of Scientific Organization - Savelieva, O. A.; Savina, O. P.; Stepanenko, V. M.; Voitovych, O. V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
Purpose. The article is aimed to prove the possibility of increasing the significance of university libraries through the services for representing the publication activity of a scientific organization. Methodology. Consideration of the possibilities of the university library to support the scientific and publishing activities of the university, namely its publication activity, was carried out on the experience of the Scientific and Technical Library of Dnipro National University of Railway Transport named after Academician V. Lazaryan (Library of DNURT). Results. The features and stages of creating / correction of the organization profile in Scopus and Web of Science databases are presented. The role of the library in scientometric studies evaluating the publication activity of university is indicated. Conclusions. The demand for university library and strengthening of its role have significantly increased as a result of the introduction of services to support the publication activity of employees and organization